BUEVA - Ammouri, Ali H. (2012)
This paper presents a novel actuator design for vibration-induced micromachining. The bi-directional ultrasonic elliptical vibration actuator (BUEVA) possesses a combination of features that renders it suitable for the machining a wide range of materials over a variety of cutting parameters. The cutting motion is an elliptical tool motion that resembles “spoon feeding”. This cutting action is in contrast to in-plane, horizontal motion utilized by most existing setups. The motion is arrived at through a combination of motions along the tool's axial and transverse directions and by vibrating out of phase and is generated by two stacked ceramic multilayer actuator ring piezo elements. Another distinguishing feature of BUEVA is the use of piezo stacks which ensure high blocking force compared to low force of piezo benders as used in many existing actuators. Furthermore, the amplitude and frequency of vibration of the tool are controlled on-line in order to vary the cutting depth and cutting speed according to the desired cutting parameters. This is a desirable characteristic which allows one to “dial-in” a desirable cutting speed for different workpiece materials. Another attractive BUEVA feature is that the design is very compact and can fit easily into the working space of most milling machining centers without the need for custom motion setups. An off the shelf TiALN-coated carbide turning tool is utilized as the cutting tool. Furthermore, refined versions of previously reported models by other workers in the micromachining field have been developed. Experimental force and surface roughness measurements are compared versus these ideal calculations from the improved models. Compared with these reference models, our refined calculations show improvements in describing chip geometry based on corrected tool motion and which, consequently, resulted in improved estimates of both surface roughness and cutting forces. Verification cutting tests in two different materials (Al2024 and Plexiglas) show good surface integrity and dimensional definition with roughness measurements in reasonable correlation to the refined model calculations.